Analysis of Implementation of E-Legislation Based on Public Participation at the National Law Development Agency - Ari Khusrini; Teguh Kurniawan (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
Previous studies of e-rulemaking that have not touched the theme of e-rulemaking in Indonesia or e-legislation, findings of the observations of the BPHN's website are technical constraints and low public comment statistics, the urgency of the needs of the Indonesian Government in improving democracy and the quality of policies, as well as the legal vacuum regarding the provision of the implementation of e-legislation since 2014 until now, hence the review of this paper will be focused on the preparation of a research framework to address the quality of implementation of public participation with e-legislation. The qualitative research method used is literature review and observation on the BPHN’s website with a study period of October 2016-January 2019. The results of the literature review show, conceptually, quality of the e-rulemaking cannot only be seen from a large number of participants, but rather to the quality of comments that has a substantial depth to get the quality of policy and compliance in its implementation. The dimension of public administration is used to photograph the stages: (i) system input; (ii) system process, including processing and managing data and information; and (iii) the quality of public comments and the policy of draft output.